Digital Marketing Strategy for MSME Development - Eliyanti Agus Mokodompit; I Nyoman Tri Sutaguna; Heriyana Heriyana; Arief Yanto Rukmana; Sri Gustini (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
MSMEs are crucial to Indonesia's economy because of their large contribution to growth. The MSME sector is one of the main pillars holding up the basis of the Indonesian economy. MSMEs and the rise of digitalization will make Indonesia the country with the largest digital economy in Southeast Asia by 2026. However, MSMEs have difficulties, the most significant of which is the need to strengthen the human capital of MSME participants and improve digital skill development. The dearth of online marketing education continues to be a problem for many MSMEs. comparable to the Hanan Boga Rasa UMKM in the Buton City neighborhood. Teachers, students, and thematic KKN Group 34 developed plans and methods to improve MSME product branding. The activities are conducted using the qualitative technique, which makes use of MSMEs' interviews, documentation, dialogue, and observation. The results of the operations also help MSMEs, since they can enhance public perception of their products and increase marketing and sales